PELEVIN'S ARTISTIC REALITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Pelevin is in fashion even now. But his books can be liked for different reasons. Some people like the dialogues, new words, sarcasm. Some like the plot or the characters. Some like the philosophy. But behind the beautiful wrapper, Pelevin always hides something more than just high-quality text. Few people dig deep and continue to love Pelevin not for the wrapper. To really understand Pelevin, you need to know the keys that he scattered, including in short stories, where the theme is almost completely revealed, and then these keys are mounted in other texts. If you still intend to get to everything yourself, then it is better not to read everything below. Also, due to the fact that Pelevin used a lot of foul language in order to better understand the meaning, all these words are forced to be used here.